Organizational creative climate & learning organization: factors contributing towards innovation within an organization - Ismail, Azahari; Ismail, Meriam; Abu Samah, Bahaman; Ahmad, Shamsuddin; Idris, Khairuddin; Uli, Jegak (Universiti Putra Malaysia Press, 2003)
Studies on innovation have suggested that a creative organizational climate tends to play an important role and is a predictor for innovation. However, lately, the presence of learning culture in an organization tends to explain a considerable influencing effect on innovation too. This particular case study tries to examine the influence of both variables on innovation and to determine which one of the two can be a better predictor for technological and organizational innovation. The results indicated that both learning culture and creative climate significantly contributed 80.4% to the variance in the innovation construct with organizational creative climate on its own, contributing 55.6% and the learning culture on its own, contributing 63.7% of the observed variances in innovation. The results of the study also found that the learning organization dimensions contributed more to the variances in innovation, particularly the dimension of 'Strategic Leadership' which had a significantly high predictive power on innovation occurring within the case organization as compared to the ten organizational creative climate factors and the rest of the six learning organization dimensions.